KONTRIBUSI USAHATANI GULA AREN TERHADAP PENDAPATAN KELUARGA DI DESA TANGKENO KECAMATAN KABAENA TENGAH (Contribution of palm sugar farming to family income in Tangkeno village, central Kabaena subdistrict) - Hafidah Nur; Rosmarlinasiah Rosmarlinasiah; Sitti Marwah; Anas Nikoyan; Satya AgustinaLaksananny; La Ode Agus Salim Mando (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2024)
Sugar palm is a type of palm plant that is almost spread throughout Indonesia. All parts of this plant can be used, starting from the sap which can be processed into sugar, and the stems can be processed into palm flour, the unripe fruit can be processed into palm fruit, and the fibers can be processed into crafts. The aim of this research is to find out how much palm sugar farming contributes to family income in Tangkeno Village, Central Kabaena District. Meanwhile, the benefit of this research is to provide information regarding how much palm sugar processing contributes to family income in Tangkeno Village, Central Kabaena District. The method used in this research is the interview method. The types of data used to conduct research are primary data and secondary data. The results of research from 38 respondents show that the average contribution to palm sugar farming income in Tangkeno Village, Central Kabaena District for one year is IDR 22.934.210 with an average amount of palm sugar production of 4.323 kilograms, so the annual contribution of palm sugar farming is by 55%. The amount of income from palm sugar farming is quite large and is able to help the family to meet their needs. Keywords: Contribution, Income, Palm Sugar Farming Business, Tangkeno Village, Central Kabaena District